A Brief Educational Intervention to Improve Healthcare Providers' Awareness of Child Passenger Safety - O. James Ekundayo; Gennifer Jones; Angela Brown; Muktar Aliyu; Robert Levine; Irwin Goldzweig (Hindawi Limited, 2013)
Introduction. Motor vehicle crashes are the leading cause of death among US children aged 4-14 years. In theory, health provider counseling about Child Passenger Safety (CPS) could be a useful deterrent. The data about the effectiveness of CPS dissemination is sparse, but existing results suggest that providers are not well informed. Moreover, there is insufficient evidence to determine whether provider counseling about CPS is effective. Methods. We therefore assessed CPS best practice knowledge among 217 healthcare workers at hospitals in seven cities throughout the USA and evaluated the impact of a brief, lunch and learn educational intervention with a five-item questionnaire. Attendees were comprised of physicians, nurses, social workers, pediatric residents, and pediatric trauma response teams. Results. Pre-post survey completion was nearly 100% (216 of 217 attendees). Participation was fairly evenly distributed according to age (18-29, 30-44, and 45+ years). More than 80% of attendees were women. Before intervention, only 4% of respondents (9/216) answered all five questions correctly; this rose to 77% (167/216) (P<0.001, using a Wilcoxon signed-rank test) after intervention. Conclusion. Future research should consider implementation and controlled testing of comparable educational programs to determine if they improve dissemination of CPS best practice recommendations in the long term.